Über Zusammenhängen des Raumes von Stützelementen - Urbonas, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Г. Урбонас, О связностях в пространстве опорных элементов A. Urbonas, Apie atraminių elementų erdvės sąryšius